2023
DOI: 10.3390/jrfm16020127
|View full text |Cite
|
Sign up to set email alerts
|

Herding Trend in Working Capital Management Practices: Evidence from the Non-Financial Sector of Pakistan

Abstract: Working capital management requires careful attention from corporate managers because it plays an important role in corporate stability. The social belongingness of managers induced them to learn from their society, colleagues, and overall industrial movement. They also learn from their peers that have more strategic efficiency. In line with these arguments, the objective of the current study is to explore the peer influence on corporate working capital management practices. For regression analysis, we utilize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…A connection coefficient is a measurable metric that evaluates how successfully one part predicts changes in another. It is reasonable to conclude that a shift in one variable results in a shift in the other when one variable's fluctuation predicts another's fluctuation (Farooq et al, 2023).…”
Section: Methodsmentioning
confidence: 98%
“…A connection coefficient is a measurable metric that evaluates how successfully one part predicts changes in another. It is reasonable to conclude that a shift in one variable results in a shift in the other when one variable's fluctuation predicts another's fluctuation (Farooq et al, 2023).…”
Section: Methodsmentioning
confidence: 98%
“…Eldomiaty et al ( 2023) identified a positive influence of well-managed working capital on increased financial performance and asset performance. Farooq et al (2023) discovered a direct influence of working capital on financial performance. Based on the aforementioned research, the following hypothesis is proposed:…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…These include the need for company managers to consider factors that can affect the financial performance of SMEs, such as accounting expenditure, advertising expenditure, liquidity, and working capital, as these factors can contribute to optimal financial performance. For future researchers, it is recommended to include additional variables to explore other factors that can influence financial performance, such as leverage (Farooq et al, 2023).…”
Section: Conclusion Suggestion and Limitationmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies carried out on working capital management in the retail sector show larger businesses generally use more effective working capital management strategies (Farooq et al, 2023). Businesses that have higher inventory turnover ratios, for instance, typically exhibit superior working capital management (Breivik et al, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%